Review of the Bangladesh Female Secondary School Stipend Project Using a Social Exclusion Framework - Schurmann, Anna T (Journal of Health, Population and Nutrition, 2009)
The Female Secondary School Stipend Project in Bangladesh was established to increase the enrollment of girls in secondary schools, thereby delaying marriage and childbearing. This analysis examined the existing data using the social exclusion framework to clarify the primary exclusionary factors that have kept girls from education: harassment, poverty, and the primacy of marriage and childbirth and explored the extent to which the project has diminished such barriers. While causality is difficult to establish, data suggest that the stipend programme has contributed to the rise in enrollment of girls in secondary schools. Questions remain as to the impact of the stipend programme on delaying marriage, empowerment of girls and women, and enhancing employment opportunities. A thorough assessment of the impact is required. The case study suggests that, if the programme design had focused on the quality and content of education and the broader economic and social context, more opportunities would have been created for social and economic participation of girls. Key words: Child marriage; Economic assistance; Education, Secondary school; Equity; Fertility; Gender; Health; Impact studies; Social exclusion; Stipend; Bangladesh doi: 10.3329/jhpn.v27i4.3393 J Health Popul Nutr 2009 Aug;27(4):505-517